Los jesuitas y las misiones de frontera del alto Perú: Santa Cruz de la Sierra (1587-1603) - Coello de la Rosa, Alexandre (Revista Complutense de Historia de América, 2008)
Many historians have stressed the marginality of Santa Cruz de la Sierra, its isolation and the bellicosity of the native population as a way to understand the character no less aggressive of the Spanish colonizers. Whereas the Indian Chiriguanes acquired hostile connotations (“warlike Indians” or “slave hunters”), the Spaniards were elevated to the category of military heroes who struggled in a frontier society. To challenge these considerations, which prioritize individual enterprises, based on the private initiative of caudillos such as Domingo de Irala, Andrés Manso, Ñuflo de Chaves or Lorenzo Suarez de Figueroa in search for the gold of Paititi or that of the Mojos, I want to put a great deal of emphasis on the formation of power groups in the cruceña society at the turn of the 17th century. The projects of conquest and colonization of such “military heroes” were the result of a network of social and religious alliances to gain political hegemony. The arrival of the Jesuits as “religious heroes” was a valuable support to wage a great number of military campaigns against the chiriguanes between 1587 and 1603 in those frontier spaces in Upper Peru.